Pharmacy Professionals’ Dispensing Practice, Knowledge, and Attitude towards Emergency Contraceptives in Gondar Town, Northwestern Ethiopia: A Cross-Sectional Study - Belachew, Sewunet Admasu; Yimenu, Dawit Kumilachew; Gebresillassie, Begashaw Melaku (International Journal of Reproductive Medicine, 2017)
Background. Pharmacy professionals, as the most available members of medical team, have an important role in educating patients about the effective and appropriate use of contraceptives. The purpose of this study was to assess pharmacy professionals’ dispensing practice, knowledge, and attitude towards emergency contraceptives use in Gondar town, northwestern Ethiopia. Methods. An institution based cross-sectional study was employed from May 14 to June 14, 2016, on 60 pharmacy professionals, who have been working in 8 randomly selected pharmacies and 6 drug stores. The collected data was entered to and analyzed using Statistical Packages for Social Sciences (SPSS) version 20. Result. More than half 33 (55.0%) of the participants were druggist with 5–9 years of experience. About 56 (93.3%) of the participants knew about the dosing schedule (when and how much to take) and side effects of emergency contraceptives. More than two-thirds of the participants (39, 65%) agreed that the existence of emergency contraceptives is a positive thing and considered their use is ethical (42, 63.3%). The majority of participants (51, 85%) also reported that they counsel all women when dispensing emergency contraceptive pills (ECPs). Conclusion. This study revealed that knowledge, attitude, and dispensing practice of emergency contraceptives are very good even though there were variations with respect to different factors. Findings suggested that additional training and proper counseling technique on emergency contraceptives will improve the service delivery.